REVISITING CUSTOMER LOYALTY IN THE CAFÉ INDUSTRY: THE ROLE OF PRICE AND LOCATION AT DOPAMINE CAFÉ J CITY MEDAN - Elfredo Hutauruk; Henri Saragih; Elperida J. Sinurat (RADJA PUBLIKA, 2025)
In Indonesia, the café business has evolved into a sophisticated social and leisure arena where factors like location and cost have an impact on patronage, but so do factors like product quality, customer service, and overall experience. This study uses a causal-associative approach based on servicescape theory to investigate how location and price affect patron loyalty at Dopamine Café J City Medan. Data were gathered from 99 customer respondents via a 1–5 Likert-scale questionnaire and analyzed using multiple linear regression (path analysis). The findings demonstrate that pricing does not significantly influence customer loyalty (β = –0.055; p = 0.310), however location exerts a significant negative impact (β = –0.112; p = 0.020), indicating that even with a strategic position, intense competition in the area promotes customer switching behavior. Concurrent analysis indicates that price and location collectively exert a significant influence on loyalty (F = 3.164; p = 0.040), accounting for merely 6.2% of the variance in customer loyalty (R² = 0.062), while the remaining 93.8% is attributable to other determinants including product quality, service, ambiance, and customer experience. These findings underscore that strategies to enhance customer loyalty in the café industry cannot rely solely on price and location, but must integrate customer experience, service quality, and value differentiation as key factors in building long-term loyalty.